Advertisement
Not a member of Pastebin yet?
Sign Up,
it unlocks many cool features!
- <thinking>
- To prove this statement, we need to follow these steps:
- 1. Understand the notation:
- - T is a linear operator
- - N(T^k) is the null space of T^k
- - R(T^k) is the range of T^k
- 2. Recall key properties of linear operators:
- - For any linear operator T, N(T^k) ⊆ N(T^(k+1)) and R(T^(k+1)) ⊆ R(T^k)
- - The dimensions of these spaces can only increase or decrease by a finite amount
- 3. Consider the ascending and descending chains of subspaces:
- N(T^0) ⊆ N(T^1) ⊆ N(T^2) ⊆ ...
- ... ⊇ R(T^2) ⊇ R(T^1) ⊇ R(T^0)
- 4. Use the fact that the vector space is finite-dimensional:
- - This means that these chains must eventually stabilize
- - There exists a k such that N(T^k) = N(T^(k+1)) and R(T^k) = R(T^(k+1))
- 5. Prove that for this k, N(T^k) ∩ R(T^k) = {0}:
- - Let x ∈ N(T^k) ∩ R(T^k)
- - Since x ∈ R(T^k), there exists y such that T^k(y) = x
- - Since x ∈ N(T^k), T^k(x) = 0
- - But T^k(x) = T^k(T^k(y)) = T^(2k)(y) = 0
- - This means y ∈ N(T^(2k)) = N(T^k), so T^k(y) = 0
- - Therefore, x = T^k(y) = 0
- <reflection>
- This proof relies on the fundamental theorem of linear algebra, which states that for any linear operator T on a finite-dimensional vector space, there exists a k such that N(T^k) = N(T^(k+1)) and R(T^k) = R(T^(k+1)). This theorem is indeed correct and widely used in linear algebra. The proof that N(T^k) ∩ R(T^k) = {0} for this k is also logically sound, using the properties of null spaces and ranges.
- </reflection>
- </thinking>
- <output>
- The proof that there exists a nonnegative integer k such that N(T^k) ∩ R(T^k) = {0} for a linear operator T on a finite-dimensional vector space can be summarized as follows:
- 1. Consider the ascending chain of null spaces N(T^0) ⊆ N(T^1) ⊆ N(T^2) ⊆ ... and the descending chain of ranges ... ⊇ R(T^2) ⊇ R(T^1) ⊇ R(T^0).
- 2. Due to the finite dimensionality of the vector space, these chains must eventually stabilize. There exists a k such that N(T^k) = N(T^(k+1)) and R(T^k) = R(T^(k+1)).
- 3. For this k, we can prove that N(T^k) ∩ R(T^k) = {0}:
- Let x ∈ N(T^k) ∩ R(T^k).
- Then there exists y such that T^k(y) = x.
- Since x ∈ N(T^k), T^k(x) = 0.
- But T^k(x) = T^k(T^k(y)) = T^(2k)(y) = 0.
- This means y ∈ N(T^(2k)) = N(T^k), so T^k(y) = 0.
- Therefore, x = T^k(y) = 0.
- Thus, we have proved that there exists a nonnegative integer k such that N(T^k) ∩ R(T^k) = {0}.
- </output>
Advertisement
Add Comment
Please, Sign In to add comment
Advertisement